Activation of transcription enforces the formation of distinct nuclear bodies in zebrafish embryos. Issue 6 (3rd June 2017) - Heyn, Patricia; Salmonowicz, Hanna; Rodenfels, Jonathan; Neugebauer, Karla M.
ABSTRACT: Nuclear bodies are cellular compartments that lack lipid bilayers and harbor specific RNAs and proteins. Recent proposals that nuclear bodies form through liquid-liquid phase separation leave the question of how different nuclear bodies maintain their distinct identities unanswered. Here we investigate Cajal bodies (CBs), histone locus bodies (HLBs) and nucleoli – involved in assembly of the splicing machinery, histone mRNA 3′ end processing, and rRNA processing, respectively – in the embryos of the zebrafish, Danio rerio . We take advantage of the transcriptional silence of the 1-cell embryo and follow nuclear body appearance as zygotic transcription becomes activated. CBs are present from fertilization onwards, while HLB and nucleolar components formed foci several hours later when histone genes and rDNA became active. HLB formation was blocked by transcription inhibition, suggesting nascent histone transcripts recruit HLB components like U7 snRNP. Surprisingly, we found that U7 base-pairing with nascent histone transcripts was not required for localization to HLBs. Rather, the type of Sm ring assembled on U7 determined its targeting to HLBs or CBs; the spliceosomal Sm ring targeted snRNAs to CBs while the specialized U7 Sm-ring localized to HLBs, demonstrating the contribution of protein constituents to the distinction among nuclear bodies. Thus, nucleolar, HLB, and CB components can mix in early embryogenesis when transcription is naturally or artificially silenced. These data support a model in which transcription of specific gene loci nucleates nuclear body components with high specificity and fidelity to perform distinct regulatory functions.